GENDER DIFFERENCES IN VOCABULARY LEARNING STRATEGIES: A STUDY ON SECOND-YEAR STUDENTS OF SENIOR HIGH SCHOOL IN PEKANBARU - Lara Puspita; Afrianto Daud; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aimed to find out the difference between male and female eleventh-grade students of Senior High School 12 Pekanbaru in vocabulary learning strategies and also to know the most and least common vocabulary learning strategies used by them. The sample of this research was taken by using the quota sampling technique. The number of students was 40 males and 40 females. The data was collected by using a questionnaire. This research used four types of vocabulary learning strategies, namely metacognitive strategies, cognitive strategies, determination strategies, and memory strategies. The result showed female students have the higher total average in vocabulary learning strategies than males. However, there was no significant difference in vocabulary learning strategies used by male and female students. Both male and female students indicated “checking bilingual dictionary” in determination strategies as the most common strategies and the least common strategies were “labeling physical object” in metacognitive strategies used by them.Key Words: Vocabulary, Vocabulary Learning Strategies, Gender